Editorial: Current Challenges of Ignatian Pedagogy - Jarosław Charchuła (Jesuit University Ignatianum in Krakow, 2021)
The Jubilee Ignatian Year began on 20 May 2021 and it will last until 31 July 2022. In the jubilee year of the Society of Jesus (Jesuits) celebrates the 500th anniversary of the conversion of St. Ignatius Loyola and the 400th anniversary of his canonization. The starting date of the jubilee is related to the anniversary of the event that took place in Pamplona on 20 May 1521, when a cannonball injured Ignatius during a battle. It altered the course of his life, marking the beginning of his conversion, and leading to the founding of the Society of Jesus. The date of the end of the jubilee coincides with the liturgical commemoration of St. Ignatius of Loyola, that commemorates the day of his death. The conversion of Ignatius was associated primarily with a change in his lifestyle. Once a vain nobleman focused on world success, he has turned into an ascetic and inner-motivated man. Under the influence of these experiences, Ignatius and his Companions founded an order and initiated the creation of a "new" spirituality.